Prospect Versus Utility - Currim, Imran S.; Sarin, Rakesh K. (Management Science, 1989)
We show how to calibrate a prospect model of decision making under risk for an individual. The prospect model is empirically compared to a utility model on two criteria, verification of the postulates of each model, and predictive accuracy. The empirical comparison is performed via three experiments. In Experiment 1, predictive accuracy of the models is compared in nonparadoxical situations, those which favor neither model. In contrast the predictions in Experiment 2 are for paradoxical choices, those which favor the prospect model. In Experiment 1, the prospect model is compared to a model comprising a utility function which permits separate risk attitudes for gain and losses, and hence is more flexible than a utility model as traditionally assessed. In contrast the utility model in Experiment 3 is assessed as is traditionally done assuming constant risk attitude across gains and losses. Several calibration procedures are contrasted across experiments. Our results show a high degree of consistency with the postulates of both models. On predictive accuracy the prospect model outperforms the utility model for paradoxical choices. However, for nonparadoxical situations there is little difference in the predictive ability of both models.